Size-Dependent Gold Nanoparticle Interaction at Nano–Micro Interface Using Both Monolayer and Multilayer (Tissue-Like) Cell Models - Yohan, Darren; Cruje, Charmainne; Lu, Xiaofeng; Chithrani, Devika B. (Nano-Micro Letters, 2015)
Gold nanoparticles (GNPs) are emerging as a novel tool to improve existing cancer therapeutics. GNPs are being used as radiation dose enhancers in radiation therapy as well as anticancer drugs carriers in chemotherapy. However, the success of GNP-based therapeutics depends on their ability to penetrate tumor tissue. GNPs of 20 and 50 nm diameters were used to elucidate the effects of size on the GNP interaction with tumor cells at monolayer and multilayer level. At monolayer cell level, smaller NPs had a lower uptake compared to larger NPs at monolayer cell level. However, the order was reversed at tissue-like multilayer level. The smaller NPs penetrated better compared to larger NPs in tissue-like materials. Based on our study using tissue-like materials, we can predict that the smaller NPs are better for future therapeutics due to their greater penetration in tumor tissue once leaving the leaky blood vessels. In this study, tissue-like multilayer cellular structures (MLCs) were grown to model the post-vascular tumor environment. The MLCs exhibited a much more extensive extracellular matrix than monolayer cell cultures. The MLC model can be used to optimize the nano–micro interface at tissue level before moving into animal models. This would accelerate the use of NPs in future cancer therapeutics.